2014
DOI: 10.2134/agronj2013.0278
|View full text |Cite
|
Sign up to set email alerts
|

Remediation/Restoration of Degraded Soil: I. Impact on Soil Chemical Properties

Abstract: Nutrient dynamics in the calcareous eroded soils of the western United States may react di erently than the acid soils in the eastern United States. e objectives of this study were to evaluate the impact of tillage practices and N treatments on changes in soil nutrient constituents. e eroded study was initiated in 2006 at the Agriculture Research Center, Hays, KS, on an Armo silt loam ( ne-loamy, mixed, mesic Entic Haplustolls). Tillage practices were no-tillage (NT) and conventional tillage (CT). Beef manure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
(58 reference statements)
5
14
0
1
Order By: Relevance
“…Greater changes in SOC with time associated with M application were most probably related to organic amendments added compared with control treatment. Mikha et al (2014) also observed an increase in SOC at the surface 0 to 15 cm due to continuous M addition.…”
Section: Results and Discussion Soil Organic Carbon And Soil Total Nmentioning
confidence: 67%
“…Greater changes in SOC with time associated with M application were most probably related to organic amendments added compared with control treatment. Mikha et al (2014) also observed an increase in SOC at the surface 0 to 15 cm due to continuous M addition.…”
Section: Results and Discussion Soil Organic Carbon And Soil Total Nmentioning
confidence: 67%
“…Remediation/restoration of eroded cropland can be achieved by adding organic amendments (e.g. manure) to replenish SOM lost through erosion [ 4 , 10 12 ]. Organic amendments also enhance microbial activity and microbial diversity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dairy manure typically increases bacterial populations and the substrate diversity for microbes (Larkin et al 2006). Judicious manure additions restore the productivity of eroded calcareous soils in both the western and central U.S. soon after application (Robbins et al 1997;Mikha et al 2014) and for years thereafter (Lentz et al 2011). Applications of manure, compost, or both provide P, K, and other nutrients to subsequent crops (Robbins et al 1997;Eghball 2002;Eghball et al 2004;Moore et al 2009).…”
Section: Introductionmentioning
confidence: 99%